The Effect of Red Fruit's (Pandanus conoideus) Extract to Eritrocytes, Hemoglobin, PCV and TPP Concentrations of Mice (Mus musculus) Infected by Toxoplasma gondii - Anis Dwi Utami; Dwi Priyowidodo (Jurnal Sain Veteriner, 2014)
Toxoplasmosis is a zoonotic parasites caused by Toxoplasma gondii. The red fruit’s extract contains tocopherol and betacarotene as antioxidant and it can repair the bodies immune system. This research was aimed to study the effect of red fruit’s extract to erithrocytes, hemoglobine, the values of PCV and TPP concentration of mice infected with T. gondii, so that the red fruit extract can be used as alternative herbal medicine for eliminating Toxoplasmosis. 15 of Balb/C mice, male, three months, 30 gr of body weight were used as experimental animals. The mice were then devided into three groups. Group I was a control, group II  was tachyzoite infected and group III was tachyzoite infected and given red fruit’s extract. Group III given red fruit’s extract on first day with 0,53 g/kg BW/mice/day. Mice in group II and III were infected by injection Toxoplasma gondii tachyziote 1x103 a mice intraperitoneally. The blood sample was taken from five mice in each group at 7th and 12th day pass through cantus medialis. The blood was examinated in Clinical Pathology Laboratory, Faculty of Veterinary Medicine, Gadjah Mada University. Data were analyzed by using Factorial 2 x 3. The result showed no significant difference (P>0,05) in hemoglobin, and PCV’s value between groups I, II and III before and after infection of T. gondii’s tachyzoite. The TPP’s value between groups I, II and III before and after infection of T. gondii’s tachyzoite was significantly difference (P<0,05).